ANALISIS LITERASI SAINS DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI PROGRAM PEMINATAN ILMU-ILMU SOSIAL (IIS) SMA NEGERI 5 PEKANBARU - Ericka Tri Maharani; Yuslim Fauziah; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the ability of students scientific literacy based on aspects of competence and knowledge as well as student achievement biology in cross biological interest of learning of class XI program of social sciences in SMA Negeri 5 Pekanbaru which was held in May until November 2019. The sample in this research were 145 students of class XI IIS in SMA Negeri 5 Pekanbaru. The instrumen used in data colletion using 2015 PISA question containing biologial content consisted of 14 questions on the topic of scientific method, biodiversity and respiratory system disorder. The results of the data analysis showed that students scientific literacy skills in aspects of competence and knowlwdge fall into the very poor category with an percentage of <54%. In the aspect of competence consists of three indicators, namely explain phenomen scientifially 43,15%, evaluate and design sientific enquiry 37,75%, and interpret data and evidence scientifically 34,48%. In the aspects of knowledge consist of three indicator namely content knowledge 44,13%, procedural knowledge 23,10%, and epistemic knowledge 34,48%. The student achievement biology with an average of 70,30 with less category. Student achievement are based in three matererials, namely the scientific method 70,20, biodiversity 72,96 and respiratory system 67,75.Key Words: Scientific Literacy, Student Ahievement Biology, Cross Biologial Interest